2009
DOI: 10.1016/j.jcta.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Matchings and independent sets of a fixed size in regular graphs

Abstract: We use an entropy based method to study two graph maximization problems. We upper bound the number of matchings of fixed size in a d-regular graph on N vertices. For 2 N bounded away from 0 and 1, the logarithm of the bound we obtain agrees in its leading term with the logarithm of the number of matchings of size in the graph consisting of N 2d disjoint copies of K d,d . This provides asymptotic evidence for a conjecture of S. Friedland et al. We also obtain an analogous result for independent sets of a fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…For α ≤ (d + 1) −2 , Corollary 3 improves the bound given by Carroll, Galvin, and Tetali in [3] 2 . Specializing to Z d (n) and Q d we get upper bounds of α (1 − log α − α(2d + 1)/2) and α (1 − log α − α(d + 1)/2) respectively on the normalized logarithm of the number of independent sets of size αn.…”
Section: The Hard-core Modelsupporting
confidence: 67%
See 1 more Smart Citation
“…For α ≤ (d + 1) −2 , Corollary 3 improves the bound given by Carroll, Galvin, and Tetali in [3] 2 . Specializing to Z d (n) and Q d we get upper bounds of α (1 − log α − α(2d + 1)/2) and α (1 − log α − α(d + 1)/2) respectively on the normalized logarithm of the number of independent sets of size αn.…”
Section: The Hard-core Modelsupporting
confidence: 67%
“…For this range of α, the best upper bound in [3] on IS(αn) is the third bound given in Theorem 1.6, 2 αn n/2 αn . On the scale of the free energy this is −α log(α) − (1/2 − α) log(1 − 2α).…”
Section: The Hard-core Modelmentioning
confidence: 96%
“…Using this Heilmann-Lieb inequality, we shall derive rigorous upper bounds for N (i) of general graphs. In the case of regular graphs they are stricter than those in [17] in a region with small dimer density; in the case of general graphs, we obtain an upper bound for the matching generating polynomial which is stricter than the one found in [18].…”
Section: Introductionmentioning
confidence: 69%
“…We have shown that this inequality leads to rigorous upper bounds for the number of matchings N (i) improving those known up to now for regular graphs [32] in the region of low dimer density, and for general graphs. In the latter case, we derive an upper bound for the matching matching polynomial improving the one in [18].…”
Section: Discussionmentioning
confidence: 99%
“…The above proof is essentially the same as the proofs in Carroll, Galvin, and Tetali with the small observation that λ can be chosen so that k is the most likely size of a matching (or independent set) drawn from Hd,n. The factor 2n in both cases can surely be improved by using some regularity of the independent set and matchings sequence of a general d‐regular graph; we leave this for future work.…”
Section: Independent Sets and Matchings Of A Given Sizementioning
confidence: 90%